2000
DOI: 10.12968/bjom.2000.8.4.8157
|View full text |Cite
|
Sign up to set email alerts
|

Breast-feeding: midwives meeting mothers in the middle

Abstract: This paper describes a qualitative study in which midwives’ perceptions of high and low quality interactions between midwives and breast-feeding mothers were elicited. Questionnaires using a critical incident technique were distributed to all the midwives in a maternity service in the North of England. Structured analysis of 16 responses (40%) led to the development of four major themes: communication, support by health professionals, inaccuracy/inconsistency of advice and breast-feeding policy. The case for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Currently, they are entrenched in the concept that ‘breast is best’ and the needs of the infant are paramount, regardless of the mother’s needs. This is exemplified in the ten steps to successful breastfeeding (WHO & UNICEF 1991), which are often applied rigidly (Stein et al. 2000, Schmied et al.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, they are entrenched in the concept that ‘breast is best’ and the needs of the infant are paramount, regardless of the mother’s needs. This is exemplified in the ten steps to successful breastfeeding (WHO & UNICEF 1991), which are often applied rigidly (Stein et al. 2000, Schmied et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although midwives themselves have identified a number of important communication skills required to support women to breastfeed, such as listening, comprehension, consistency and good non‐verbal communication (Stein et al . 2000), it has been identified that health care professionals are often unable to provide the support women need (Coreil et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is suggested that current policies and practices are often applied rigidly (Stein et al . 2000; Schmied et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations